CPA Firm Viability: A Study of Major Environmental Factors Affecting Firms of Various Sizes and Characteristics. - Burns, Thomas J.; Dillard, Jesse F. (The Accounting Review, 1981)
Reviews the book "CPA Firm Viability: A Study of Major Environmental Factors Affecting Firms of Various Sizes and Characteristics," by Harold E. Arnett and Paul Danos.